Tambang Ilegal di Kabupaten Kutai Kartanegara Terkait Dengan Undang-Undang Nomor 3 Tahun 2020 tentang Perubahan Atas Undang-Undang Nomor 4 Tahun2009 tentang Pertambangan Mineral dan Batu Bara - Jefri Anthoni; Hendrich Jut Abert; Ety Sandora (Collegium Studiosum Journal, 2020)
According to the Mining Advocacy Network (JATAM) of East Kalimantan, there are 151 illegal mines operating in 4 areas of East Kalimantan, this is very worrying and since mining permits are in the center, the local government is increasingly indifferent, they are increasingly empowered to dig without a permit. The issue of Illegal Coal Mining in East Kalimantan is currently a problem that must be resolved together. Because this problem has become a problem at the national level. Currently there are around 100 more illegal mines that must be completed by local law enforcement officers in the Bumi Etam area, especially in Kutai Kartanegara Regency. The author uses the library research method or literature review. This literature review research is conducting research from library books, magazines, journals and articles and sources from the internet that are relevant to the problems discussed.